2018
DOI: 10.5539/jas.v10n9p430
|View full text |Cite
|
Sign up to set email alerts
|

Techniques for Quality Control in Football Field Located in Agricultural Area

Abstract: A set of eight sprinklers was evaluated in a soccer field located in the city of Cascavel, Paraná, Brazil, using quality control techniques. The graph X (Shewhart's individual control card), the EWMA graph (exponentially weighted moving average) and the CUSUM tabular graph (cumulative sum) were used. The system was composed of two parallel lateral lines distanced of 18 meters, containing five sprinklers in each line every 18 meters. The first four sprinklers (area A) and the last four (area B) were evaluated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…Through r 2 , it is also possible to attest that wind speed is the variable with highest correlation (r) with the distribution uniformity given by CU. Siqueira et al (2018) also found similar results when evaluating a sprinkler system for a soccer field, in Brazil. These authors verified that wind speed was the variable with the strongest effect on distribution uniformity.…”
Section: Resultssupporting
confidence: 65%
See 2 more Smart Citations
“…Through r 2 , it is also possible to attest that wind speed is the variable with highest correlation (r) with the distribution uniformity given by CU. Siqueira et al (2018) also found similar results when evaluating a sprinkler system for a soccer field, in Brazil. These authors verified that wind speed was the variable with the strongest effect on distribution uniformity.…”
Section: Resultssupporting
confidence: 65%
“…The grass for soccer fields, golfing, gardens and many others occupies large expanses of land and are highly sensitive to water deficit, requiring an appropriate irrigation management throughout the year. The water, when supplied in the right moment and quantity, guarantees that the grass field will be maintained in ideal conditions for proper practice of sports and aesthetic purposes (García-González et al 2015;Siqueira et al 2018). Thus, an adequate irrigation system presents itself as a relevant strategy to achieve these goals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sequences of six points in the descending order characterize an out of statistical control process (Montgomery, 2016). The EWMA control chart is the most suitable for micro irrigation assessment, as it detects minor variations in the process (Siqueira et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…For analysis of parameters, such as uniformity, statistical control techniques such as control charts can be applied. Studies on quality control in irrigation have been the focus of some research, such as those by (Frigo et al 2013), (Hermes et al 2015), (Zocoler et al 2015), (Andrade et al 2017), (Siqueira 2018) and (Lopes et al 2021b). It is noteworthy that, from the use of this technique, the authors obtained important results for the improvement of the process.…”
Section: Introductionmentioning
confidence: 99%